Stability and stabilization of biocatalysts : proceedings of an international symposium organized under auspices of the Working Party on Applied Biocatalysis of the European Federation of Biotechnology, the University of Cordoba, Spain, and the Spanish Society of Biotechnology, Cordoba, Spain, April 19-22, 1998 /: proceedings of an international symposium organized under auspices of the Working Party on Applied Biocatalysis of the European Federation of Biotechnology, the University of Cordoba, Spain, and the Spanish Society of Biotechnology, Cordoba, Spain, April 19-22, 1998. (1998) - Unknown
No abstract available